PROXIMATE COMPOSITION OF FIVE SPECIES OF FLAT FISHES - KESHAVA, N; SEN, D P (Fishery Technology, 2017)
Five species of flat fishes, namely, Cynoglossus semifaciatus, C. !ida, C. bilineatus, C. macrolepidotus and Psettodes erumei caught in trawlers off Mangalore were analysed for proximate composition of different body parts. These data are discussed interms of their variability and applications. In whole body of C.lida and C. semifaciatus mean values for moisture, protein, fat and ash content on dry basis respectively were 75.9%, 75.3%. 7.1%, 16.1% and 78.9%, 75.6%. 7.9% and 16.6%. Mean values of these constituents of edible parts in the same order for C. semifaciatus and Psettodes erumei were 77.3%, 80.7%, 7.8%, 10.8% and 77.4%, 86.2%, 3.5% and 11.1% respectively.